(untitled) (Annual of the Faculty of Philosophy in Skopje, 2019)
Macular degeneration (MD) involves a whole range of progressive and degenerative changes in the macula. Though central vision is affected, peripheral vision usually remains preserved in MD. Unfortunately, there is a lack of effective medical treatment for most MD, therefore it is important to focus efforts on the development of visual compensatory mechanisms. People with macular degeneration experience difficulties in reading due to central-field loss. Reading skills is the primary difficulty and at the same time the primary goal for individuals with macular degeneration seeking vision rehabilitation. The current prevalent methods for reading skills training are magnification— large print size and scotoma awareness training. Also, more recent studies showed that specific oculomotor training, avoiding visual crowding and special fonts are all beneficial to reading skills rehabilitation. The focus of this article is to review and discuss the methods and adaptations available today that we can use in rehabilitation of reading skills in individuals with MD.